Wind tunnel experimental research on the effect of col topography on wind environment - Liu Hui, (Universiti Kebangsaan Malaysia, 2016)
Investigation of meteorological disasters caused by small-scale topography shows that flashover due to wind age yaw occurred quite often where col topography existed. Considering that the distribution pattern of wind profile at different locations of a col topography is not clear, this paper, with wind tunnel tests, studied the influenced of such topographic features of a col as hill slope and valley mouth width on the wind profile at different locations. The results of wind tunnel tests indicated that over-hill wind has a stronger effect on wind velocity correction coefficient than does valley wind, that compared to flat terrain wind velocity, the maximum speed-up amplitude of wind velocity at valley throat and hill summit reach 33 and 53%, respectively, apparently higher than 10% specified in Codes, that wind velocity at valley throat increases with the increase of hill slope and decreases with the increase of valley mouth width, that wind velocity in the valley basically does not go up when the slope of one hill side is smaller than 0.1 and that wind velocity at the same non-dimensional height of a 3D hill summit increases with the increase of hill height.